2018
DOI: 10.1080/14616734.2018.1555602
|View full text |Cite
|
Sign up to set email alerts
|

Maternal reflective functioning, interpersonal violence-related posttraumatic stress disorder, and risk for psychopathology in early childhood

Abstract: The aim of this study was to examine associations between maternal mentalization, interactive behavior and child symptoms in families in which mothers suffer from interpersonal violence-related posttraumatic stress disorder (IPV-PTSD). Fifty-six mothers and children (aged 12-42 months) including mothers with a diagnosis of IPV-PTSD were studied. Mentalization was measured by the Parental Reflective Functioning (PRF) Scale. Interactive behavior during free-play was measured via the CARE-Index. Child symptoms we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 83 publications
4
33
0
Order By: Relevance
“…Accuracy of parental mentalization is one determinant of children’s emotion understanding (Karstad, Wichstrøm, Reinfjell, Belsky, & Berg-Nielsen, 2015 ). It was also demonstrated that traumatized mothers displayed poorer parental reflective functioning than non-traumatized controls (Borelli et al, 2019 ; Suardi et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accuracy of parental mentalization is one determinant of children’s emotion understanding (Karstad, Wichstrøm, Reinfjell, Belsky, & Berg-Nielsen, 2015 ). It was also demonstrated that traumatized mothers displayed poorer parental reflective functioning than non-traumatized controls (Borelli et al, 2019 ; Suardi et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, that being said, the children of traumatized mothers by the time they reached school-age did manage to acquire sufficient emotional comprehension skills to perform as controls did on the TEC. Several prior studies have shown that children of mothers with PTSD tend to have both more externalizing and internalizing symptoms (Greene, Chan, McCarthy, Wakschlag, & Briggs-Gowan, 2018 ; Suardi et al, 2018 ). The present study supports those prior observations.…”
Section: Discussionmentioning
confidence: 99%
“…Our longitudinal findings suggest that maternal IPV-PTSD during the period of child development (i.e., toddlerhood) exert an influence on the development of psychopathology in school-aged children. It is also conceivable that maternal IPV-PTSD, particularly when comorbid with major depressive symptoms, may contribute to the progression of early childhood expression of symptoms that we have described in a previous paper as a dysregulated "attachment disturbance" or "secure base distortion" (50,51) to separation anxiety disorder at school-age. Moreover, mothers' IPV (i.e., partner violence) was associated with child psychopathology, independently of PTSD.…”
Section: Discussionmentioning
confidence: 84%
“…It has been suggested that high certainty about the child's mental states may in fact represent a maladaptive pattern of intrusive mentalizing or hypermentalizing by the parent (Luyten et al, 2017). High levels of certainty about the child's mental states and intrusive mentalizing have previously been documented among mothers with PTSD (Suardi et al, 2020), as well as mothers and fathers with Attention Deficit and Hyperactive Disorder (ADHD; Mazzeschi et al, 2019). This suggests that high levels of mental distress may be associated with a tendency to hypermentalize on the child, presumably as a compensatory mechanism for the innate uncertainty embedded in the parent-child relationship (Mazzeschi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%